Alcohol’s acute effects on emotion recognition and empathy in heavy-drinking young adults - Lakshmi Kumar; Kasey G. Creswell; Kirk W. Brown; Greta Lyons; Brooke C. Feeney (Scientific Reports)
Abstract Alcohol intoxication can lead to both positive and negative social outcomes, and recent research suggests that alcohol-induced changes in emotion recognition and empathy may underlie these consequences. However, methodological limitations of prior studies make drawing firm conclusions difficult. This study addresses some of these limitations by investigating the acute effects of alcohol on emotion recognition and empathy in a large sample of young adults, using an intoxicating alcohol dose and more ecologically valid tasks. Participants (N = 156, mean age = 22.51 ± 2.16, 31.41% female, 72.44% White) were randomly assigned to groups of 3 unacquainted persons; each group was randomly assigned to drink an alcoholic or placebo beverage together. Participants then completed measures of emotion recognition and empathy. Alcohol (vs. placebo) participants showed impaired recognition of anger (B = -0.18, p < 0.01) but no other specific emotions. They additionally reported higher affective empathy (i.e., how well participants related to another participant) in response to direct interactions with other participants (B = 0.31, p < 0.05). Alcohol and placebo participants did not differ on perceived empathy assessed by a traditional third-person empathy task using static images. These effects held when controlling for covariates. Findings suggest alcohol worsens anger recognition and increases perceptions of relating to another. Results also highlight the importance of considering the nature and reliability of social cognition assessments when examining alcohol intoxication effects.